Penerapan Uji Proporsionalitas Dalam Kasus Pembubaran Partai Politik: Sebuah Perbandingan - -, Bisariyadi (UI Scholars Hub, 2018)
The Indonesian Constitutional Court has no jurisprudence related to the application of proportionality test. In comparative law perspective, proportionality test is referred to as